Residues from the thermal conversion of waste from the meat industry as a source of valuable macro- and micronutrients - Staroń, Paweł; Kowalski, Zygmunt; Staroń, Anita; Seidlerová, Jana; Banach, Marcin (Waste management (New York, N.Y.), 2016)
The increased consumption of meat (including poultry) observed over the last decade has led to the intensification of its production. With the production increase, the amount of generated waste also increases. Appropriate disposal of waste from the meat industry will significantly reduce the amount of such waste and its negative impact on the environment. The paper presents a method for the thermal neutralisation of feathers, poultry litter and meat and bone meal (MBM). Waste incineration was carried out in a stationary electric furnace, at a temperature varying in the range of 600-900°C. The resulting ashes were characterised by a high percentage of phosphorus (30-170 g/kg ash), calcium (20-360 g/kg ash) and other valuable macro- and micronutrients like copper, iron, manganese and zinc. The ashes produced during the thermal treatment are safe in terms of sanitary and can be used as additives enriching the fertilisers and soil improvers.
Keywords: Meat; popel uhelný; peří; mikroživiny; hnůj; Phosphorus; Coal Ash; Incineration; Micronutrients; Manure; Biological Products; Animals; Poultry litter; spalování odpadů; zvířata; průmysl zpracování potravin; Food-Processing Industry; minerály; Resource recovery; Meat–bone meal; maso; Minerals; Feathers; biologické přípravky